Integritas dan Profesionalisme: Kajian Implementasi Kode Etik Pustakawan di Unit Pelaksana Teknis Perpustakaan UIN Sulthan Thaha Jambi - Raudhoh, Raudhoh; Agustin, Tri (Syarif Hidayatullah State Islamic University of Jakarta, 2024)
The attitude of librarians in providing services or collaboration between librarians and institutions as well as contributions to libraries is very closely related to the implementation of the librarian's code of ethics. In its implementation, it is known that the librarian code of ethics are rules or norms that must be obeyed by librarians to maintain their dignity, image and profession in providing services to users. This research aims to find out how the librarian code of ethics is implemented, in the Technical Implementation Unit (UPT) of the Sulthan Thaha Saifuddin Jambi State Islamic University Library. The method used in this research is descriptive qualitative. The technique used in determining informants is purposive sampling or direct determination. Meanwhile, data collection techniques are through observation, interviews and documentation at the UPT Library of the Sulthan Thaha Saifuddin Jambi State Islamic University. The results of this research show that. the implementation of the librarian code of ethics at the UPT UIN Sulthan Thaha Saifuddin Jambi Library is not optimal. This can be seen from the fact that several codes of ethics cannot be implemented in accordance with the rules and norms contained in the code of ethics. The obstacle faced is that librarians do not yet realize the importance of implementing a code of ethics in carrying out their duties. Efforts have been made by the head of the library by holding further training or training for librarians so that librarians increase their knowledge and insight into the code of ethics so that they are expected to be able to implement the code of ethics. Meanwhile, the efforts made by librarians are to deepen knowledge regarding the duties and functions of being a librarian and increase skills so that they can improve performance and implement the code of ethics.